In vitro evaluation of ahorchataa co-products as carbon source for probiotic bacteria growth - Sanchez-Zapata, Elena; Fernandez-Lopez, Juana; Perez-Alvarez, Jose A; Soares, Jose; Sousa, Sergio; Gomes, Ana MP; Pintado, Manuela ME (Food and bioproducts processing, 2013)
Tiger nut milk (ahorchataa) liquid co-products (TNLC) were evaluated as carbon source for probiotic bacteria (Lactobacillus acidophilus and Bifidobacterium animalis) growth by screening via microplate assay and determination of viable cells and metabolic activity. Based on MRS five different basal media were prepared ((i) without carbon source, (ii) with 2% (w/v) glucose, (iii) with 2% (w/v) FOS, (iv) with 2% (v/v) TNLC and (v) 3% (v/v) TNLC). Additionally, reconstituted TNLC was also used as basal medium. For determination of viable cells and metabolic activity skim milk powder was used. Glucose was found to be the best substrate to L. acidophilus grows, followed by FOS and TNLC (2% and 3%, respectively). TNLC (3%) was found to be the best substrate followed by TNLC (2%), glucose and FOS, in the promotion of growth of B. animalis. The growth of L. acidophilus and B. animalis in skim milk reconstituted TNLC + water was higher than samples inoculated in skim milk reconstituted only with water (p < 0.05). This is supported by the pH effect and by the faster organic acid production (mainly lactic acid, acetic acid, and butyric acid), confirming the property of TNLC as a carbon source for probiotic bacteria growth.